Handbook on agriculture, biotechnology and development - edited by Stuart J. Smyth (Cheltenham Edward Elgar, 2014)
This book is a compendium of knowledge, experience and insight on agriculture, biotechnology and development. Beginning with an account of GM crop adoptions and attitudes towards them, the book assesses numerous crucial processes, concluding with detailed insights into GM products. Drawing on expert perspectives of leading authors from 57 different institutions in 16 countries, it provides a unique, global overview of agbiotech following 20 years of adoption. Many consider GM crops the most rapid agricultural innovation adopted in the history of agriculture. This book provides insights as to why the adoption has occurred globally at such a rapid rate.
Includes bibliographical references and index.
Keywords: Agricultural biotechnology